Analyzing the influence of satisfaction of basic psychological needs on sports performance among college student athletes - Haidong, Liu; Adam Assim, Mohamad Ibrani Shahrimin; Yaacob, Azhar; Tengku Kamalden, Tengku Fadilah (Editorial Salud, Ciencia y Tecnologia, 2024)
Background and Objective: more information of the determinants of sports injuries, specifically the potential variables is essential considering the increasing prevalence of these injuries among athletes to take preventative measures. This study aims to investigate the relationships between emotions related to stress, sports-related injuries, psychotherapy, flexibility of the coach to athlete relationships (FCAR), BPN frustration (BPNF) and the basic psychological needs (BPNs) satisfaction. The BPN method and the philosophical framework for stress and physical impact are the primary issues of inquiry. Method: employing a questionnaire that participants completed themselves, sports injuries and emotions related to stress were evaluated throughout the first and second months of the investigation. The third and fourth month’s study variables BPN satisfaction and BPN frustration (BPNF) were assessed by a questionnaire given to 300 college-level athletes. The fifth and sixth months of assessment evaluated psychotherapy and FCAR. In this investigation, path analysis and statistical analysis using the Jeffreys’s Amazing Statistics Program (JASP) setup are conducted. Results and Conclusion: according to this research, stress is associated with injuries related to sports while BPN satisfaction adversely affects them. Disappointment of BPN, nevertheless, does not. Basic psychological needs theory (BPNT) provides more justifications for injury-associated variables.